The tort liability for common jurisprudence and current Spanish legislation (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2012)
When the people are several the calls to be responsible for a same damage the question of the civil responsibility takes a new dimension that demands an independent and specialized legal treatment. In effect, in case of finding to us before the one assumption he makes specific illicit obligatory legal relation derived from a civil fact with object unit and plurality of creditors the question that considers is if the creditor could demand the totality of the benefit to each one of indebted - solidarity, or ifthe debit will be divided in the so many parts whatever is the indebted ones- joint obligation. For that reason, we will approach the treatment that as much the jurisprudence as the legislation has granted to the subject.
Keywords: Civil responsibility; shared in common obligations; joint obligations; jurisprudence; legislation